Application of cold thermal energy storage (CTES) for building demand management in hot climates. (25th June 2016) - Comodi, Gabriele; Carducci, Francesco; Nagarajan, Balamurugan; Romagnoli, Alessandro
Highlights: A new index, Savings per energy unit, is defined to assess the effectiveness of CTES. CTES systems were used to perform demand management strategies, removing partial load operations and shaving peak loads. CTES was used to perform price arbitrage, exploiting the difference between peak and off peak electricity rates in Singapore. Results showed that it is possible to enhance the efficiency of the whole system, achieving both energy and economic savings. Depending on the sizing scenario, the pay back periods ranged from a minimum of 8.9 years to a maximum of 16 years. Abstract: This paper investigates the feasibility of Cold Thermal Energy Storage (CTES) for building demand management applications in hot climate characterized by a cooling season lasting all year long. An existing office building, located in Singapore, serves as case study. The CTES is coupled to the existing cooling systems in order to address the opportunity of improving overall energy efficiency and to perform price arbitrage, exploiting the spread between peak and off-peak energy tariffs. Six different sizes for the CTES are analyzed, addressing different percentage of the daily cooling energy demand. A new index, Savings per energy unit, is defined to assess the effectiveness of CTES. Results indicate that it is possible to enhance the efficiency of the whole cooling system, achieving both energy and economic savings. The payback periods of the different solutions range from a minimum of 8.9 years to a maximum of 16 years. All these aspects make CTES applications a viable option. However, a large amount of space in direct proximity to the building is necessary and, especially in largely urban environment, this is not always available.